Management of Unilateral Uterine Horn Prolapse in a Full term Pregnant Great Dane Bitch - Devarajan, Reena; Seerangan, Rangasamy; Jayakumar, Umamageswari; Ragunathan, Rajalakshmi; Karuppasamy, Krishnakumar (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Uterine prolapse, the eversion of the uterine body through  the dilated cervix via the vagina, is manifested by a  hanging tubular mass out of the vulva. It is an uncommon  complication of peripartum or postpartum bitches, usually  occurs within 48 hours of whelping and involves one or both  uterine horns with distinctly visible prolapsed uterine horn  bifurcation outside the vulva (Sathiamoorthy et  al., 2013;  Battaglia and Steele, 2015). The present communication  reports the successful management of peripartum unilateral  uterine prolapse in a Great dane bitch by manual reduction  and reposition.
Keywords: Uterine prolapse; Gynaecology; Pregnant Great Dane Bitch